Gain without Pain? Non-Tariff Measures, Plants’ Productivity and Markups - Cali, Massimiliano; Le Moglie, Marco; Presidente, Giorgio (World Bank, Washington, DC, 2021)
This paper studies how productivity and markups respond to non-tariff measures. The analysis uses a novel time-varying data set on all non-tariff measures applied to imported products by Indonesia. Price and quantity information is used to disentangle the impact of non-tariff measures on plants’ technical efficiency and markups. The findings show that on average, non-tariff measures generate fewer distortions than import tariffs do. However, while specific non-tariff measures increase the quality of the products on which they are applied, others act as barriers to trade similar to import tariffs. These results suggest that to gauge their impacts and guide policy making, non-tariff measures should not be bundled together in empirical analyses.